问题 解答题
怎样简便怎样算:
(25+
4
5
)÷
1
5
4÷[(
5
9
-
4
27
)×
3
11
]
9
10
÷[
4
7
×(
3
4
-
2
5
)]
13
27
×
5
9
+
14
27
÷
9
5
25×
7
24
10
17
×[(
2
3
+
3
4
)÷
5
12
].
答案

(1)(25+

4
5
)÷
1
5

=(25+

4
5
)×5

=25×5+

4
5
×5

=125+4

=129;

(2)4÷[(

5
9
-
4
27
)×
3
11
]

=4÷[

11
27
×
3
11
]

=4÷

1
9

=4×9

=36;

(3)

9
10
÷[
4
7
×(
3
4
-
2
5
)]

=

9
10
÷[
4
7
×
7
20
]

=

9
10
÷
1
5

=

9
10
×5

=

9
2

(4)

13
27
×
5
9
+
14
27
÷
9
5

=

13
27
×
5
9
+
14
27
×
5
9

=(

13
27
+
14
27
)×
5
9

=1×

5
9

=

5
9

(5)25×

7
24

=(24+1)×

7
24

=24×

7
24
+
7
24

=7+

7
24

=7

7
24

(6)

10
17
×[(
2
3
+
3
4
)÷
5
12
]

=

10
17
×[
17
12
×
12
5
]

=

10
17
×
17
5

=2.

选择题
单项选择题